Justifikasi Qiraat Di Dalam Manuskrip Ta'mim Al Manafi' Bi Qiraat Al Imam Nafi' Karangan Al Tarmasi - Hayati Hussin; Abdul Rahim Ahmad; Zainora Daud; Muhammad Lukman Ibrahim (Research Centre for al-Quran and al-Sunnah, Faculty of Islamic Studies, UKM, 2024)
Non-Indexed Publication